Hereditary Heparin Cofactor II Deficiency and the Risk of Development of Thrombosis - Bertina, R M; van der Linden, I K; Engesser, L; Muller, H P; Brommer, E J P (Thrombosis and Haemostasis, 1987)
Heparin cofactor II (HC II) levels were measured by electroimmunoassay in healthy volunteers, and patients with liver disease, DIC, proteinuria or a history of venous thrombosis. Analysis of the data in 107 healthy volunteers revealed that plasma HC II increases with age (at least between 20 and 50 years). HC II was found to be decreased in most patients with liver disease (mean value: 43%) and only in some patients with DIC. Elevated levels were found in patients with proteinuria (mean value 145%). In 277 patients with a history of unexplained venous thrombosis three patients were identified with a HC II below the lower limit of the normal range (60%). Family studies demonstrated hereditary HC II deficiency in two cases. Among the 9 heterozygotes for HC II deficiency only one patient had a well documented history of unexplained thrombosis. Therefore the question was raised whether heterozygotes for HC II deficiency can also be found among healthy volunteers. When defining a group of individuals suspected of HC II deficiency as those who have a 90% probability that their plasma HC II is below the 95% tolerance limits of the normal distribution in the relevant age group, 2 suspected HC II deficiencies were identified among the healthy volunteers. In one case the hereditary nature of the defect could be established.It is concluded that hereditary HC II deficiency is as prevalent among healthy volunteers as in patients with thrombotic disease. Further it is unlikely that heterozygosity for HC II deficiency in itself is a risk factor for the development of venous thrombosis.
Keywords: Heparin cofactor II deficiency; Thrombosis